Role of the distal nephron on salt homeostasis and blood pressure regulation - Lim, Heeju (2021)
The distal nephron is constituted by the distal convoluted tubule, connecting tubule, and collecting duct. It is also known as “aldosterone sensitive distal nephron” (ASDN) because it is the anatomical substrate for the classical aldosterone effect of reabsorbing sodium and excreting potassium. This region is thought to perform the “fine-tuning” of ions and water homeostasis to balance intake levels. Consequently, this segment has significant impacts on sodium reabsorption and blood pressure regulation, illustrated by some genetic alteration effects such as Liddle syndrome, pseudohypoaldosteronism, and Pendred syndrome. In this mini-review, we explore the ASDN structure and the main channels that participate in sodium and chloride reabsorption. The epithelial sodium channel (ENaC) and the interchanger chloride-bicarbonate transporter (pendrin) are reviewed in detail as the main drivers of salt reabsorption in this segment. We also provide an introduction to crosstalk communication between the connecting tubule and the afferent arteriole as a feedback mechanism to integrate tubular sodium handling in this segment, in addition to its role in renal hemodynamics autoregulation.